JUSTICE FOR THE CONSUMER GARDEN PART OF IMPLEMENTATION OF LEGAL METROLOGY BY BUSINESS ACTIVITIES - Soeharsono (Sekolah Tinggi Ilmu Hukum Awang Long, 2018)
Substantial justice is important for consumers who are in fact Indonesian people when obtaining a product that must be carried out through a legal metrology process. Definition of legal metrology according to Law Number 2 of 1981 concerning Legal Metrology: Article 1 (a) Metrology is the science of measuring broadly. The author in this study focuses more on the enforcement of substantial justice against violations in the field of legal metrology, both criminal violations, violations that lead to compensation claims and administrative sanctions against business actors that harm consumers. The problem is why do violations often occur in the field of legal metrology in Indonesia? How is substantial justice reflected in consumer legal protection against legal metrology violations? And what is the responsibility of the business actor for violations in the field of legal metrology that corresponds to substantial justice? Research Methods in this Dissertation use juridical-normative research. The results of his research are substantial justice reflected in the legal protection of consumers against violations of legal metrology, in terms of legal justice and certainty can not be achieved in terms of imposing sanctions in violations of legal metrology. Often talking about justice is always concerned with philosophical issues, abstract justice and imaginative reality. Where justice should be contained in concrete sociological realities in society. Speaking of sanctions in violation of legal metrology, the author argues based on the juridical principle of the application of the Legal Metrology Law as part of the instrument of legal regulation in the economic field. As explained in the background section, the Legal Metrology Law is one type of law that is very influential in national welfare-based national development, and also mandates that the implementation of metrological activities in Indonesia is aimed at realizing legal certainty and justice.